2014
DOI: 10.1179/2042645314y.0000000083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EMC and durability of heat treated wood from high versus low water vapour pressure reactor systems

Abstract: A large number of different heating technologies has been put into use for industrial scale thermal modification of wood. A useful classification of these processes is by the level of water vapour pressure, which ranges from vacuum to high saturated steam pressures. Only high water vapour pressure systems can maintain a finite moisture content during the heat treatment, but little is known about the water vapour pressure dependence of the thermal modification chemistry and the resulting modified wood propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Heating at high temperatures (over 200°C) and low water activity, results in dry thermolysis, with the pressure making little contribution to the variables and the main controlling factor being the process temperature. Wet processes operate at lower temperatures (160-180°C) in saturated steam, with the necessary moist conditions ensured by control of temperature and pressure, although pressure is the most important parameter when determining mass loss (before and after post-treatment leaching) [22,23]. Saturated steam is in equilibrium with liquid water at the same temperature and pressure, whereas superheated steam is dry water vapour that has been heated above its saturation point.…”
Section: Description Of Process Conditionsmentioning
confidence: 99%
“…Heating at high temperatures (over 200°C) and low water activity, results in dry thermolysis, with the pressure making little contribution to the variables and the main controlling factor being the process temperature. Wet processes operate at lower temperatures (160-180°C) in saturated steam, with the necessary moist conditions ensured by control of temperature and pressure, although pressure is the most important parameter when determining mass loss (before and after post-treatment leaching) [22,23]. Saturated steam is in equilibrium with liquid water at the same temperature and pressure, whereas superheated steam is dry water vapour that has been heated above its saturation point.…”
Section: Description Of Process Conditionsmentioning
confidence: 99%
“…Thermal modification of wood has often been performed at atmospheric pressure together with superheated steam where volatile degradation products are allowed to evaporate, and severe drying takes place (Militz and Altgen 2014). The modification process can also take place in a closed reactor system, which accelerates thermal degradation and enables the regulation of the water vapor pressure and the RH during the modification process (Willems et al 2015;Altgen et al 2016c). Altgen et al (2016c) showed for European beech (Fagus sylvatica L.) wood that the mass loss (ML) obtained in a closed reactor system is a function of the maximum vapor pressure, and less dependent on the peak temperature ( 180°C) applied.…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment of wood is generally performed at temperatures ranging from 160 to 260 °C. To avoid wood combustion, heat treatment is performed in a low-oxygen environment, such as under steam conditions, nitrogen, oil, and, more recently, in a vacuum (Hakkou et al 2005;Ding et al 2011;Allegretti et al 2012;Cao et al 2012a;Dubey et al 2012;Willems et al 2015). Heat treatment has also been performed under air conditions (Aydemir et al 2012;Jiang et al 2014).…”
Section: Introductionmentioning
confidence: 99%